PENGARUH LATAR BELAKANG EKONOMI KELUARGA TERHADAP MINAT BERWIRAUSAHA MAHASISWA PROGRAM STUDI PENDIDIKAN EKONOMI UNIVERSITAS NEGERI SURABAYA - Purwaningrum, Widyawati; Tjipto Subroto, Waspodo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the influence of family economic background specifically parental income, parental occupation, and family financial support on the entrepreneurial interest of Economic Education students at the State University of Surabaya. The study utilized a total sampling technique involving a population of 233 students from the 2020, 2021, and 2022 cohorts. The results indicate that family economic background has a significant simultaneous effect on students' entrepreneurial interest (F = 50.699; p = 0.000), contributing 30.6% (R²) to the variance. Family financial support proved to be the dominant factor (β = 0.536) compared to parental income (β = 0.114). However, no significant difference in entrepreneurial interest was found between students whose parents are entrepreneurs and those whose parents are not (t = 0.702; p = 0.484). These findings underscore that financial and moral support from the family is more crucial than economic status or parental profession in shaping students' entrepreneurial interest.